2016
DOI: 10.17221/720/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant density and nitrogen rate on lodging-related stalk traits of summer maize

Abstract: Stalk lodging is a major constraint to limit grain yield under increased planting density in modern maize (Zea mays L.) production. A 3-year field experiment was imposed to study the effects of plant density and nitrogen (N) rate on stalk lodging and lodging-related stalk traits of two maize hybrids of contrasting susceptibility to lodging. The results indicated that the stem diameter, rind penetration strength (RPS), bending strength (BS), rind thickness, vascular bundle sheath's thickness (Vbs) and number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…A decrease in plant lodging from an increasing N dose might be due to an increase in the activity of the key enzymes regulating the lignin biosynthesis, lignin content, and stalk diameter [53,59]. Moreover, the thickness of the rind number and thickness of the vascular bundle is negatively correlated to stalk lodging [53]. As in our study, significant low stalk lodging was reported in maize at 120 kg ha −1 N and a similar plant density [53].…”
Section: Plant Lodging and Sterilitysupporting
confidence: 78%
See 3 more Smart Citations
“…A decrease in plant lodging from an increasing N dose might be due to an increase in the activity of the key enzymes regulating the lignin biosynthesis, lignin content, and stalk diameter [53,59]. Moreover, the thickness of the rind number and thickness of the vascular bundle is negatively correlated to stalk lodging [53]. As in our study, significant low stalk lodging was reported in maize at 120 kg ha −1 N and a similar plant density [53].…”
Section: Plant Lodging and Sterilitysupporting
confidence: 78%
“…Moreover, the thickness of the rind number and thickness of the vascular bundle is negatively correlated to stalk lodging [53]. As in our study, significant low stalk lodging was reported in maize at 120 kg ha −1 N and a similar plant density [53]. Additionally, they reported, N application increased stem characteristics such as rind thickness, number, and thickness of vascular bundle and found a similar effect at 120 kg ha −1 N and 180 kg ha −1 N.…”
Section: Plant Lodging and Sterilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Under this condition, plants invest more resources in elongation in an attempt to outgrow the crop canopy to escape shading and consequently have a reduced stem diameter (Taiz & Zeiger, 2017). In this situation, N supply can improve the stem quality and decrease etiolation caused by higher plant densities, although only up to a certain point (Shi et al, 2016), as observed in growing season 2 (Figure 2D).…”
Section: Figurementioning
confidence: 88%